The Using of Organic Acids in California Turkey Chicks and its Effects on Performance Before Pasturing - Celik, Kemal; Ersoy, I. Erbil; Uzatici, Ahmet; ERTURK, Mustafa (International Journal of Poultry Science, 2003)
The experiment described evaluated the effect of a commercial in-feed preparation (Biotronic® SE) involving a mixture of organic acids and salts on California turkey chicks performance. In these experiments, 1-d-old commercial white turkey poults were placed into battery brooders and were given turkey starter feed and water ad libitum. Biotronic® SE had very small effect on the body weight gain (BWG) when included in the feed and live bird performance was not adversely affected by feeding up to 2.0%. from 0 to 60 days as based groups.